Cutting edge: cross-presented intracranial antigen primes CD8+ T cells. - Walter, Lisa; et al. (Journal of Immunology, 2007)
The CNS is considered immune privileged due to the blood-brain barrier and the absence of conventional lymphatics. Nonetheless, T cell immune responses specific for CNS Ag have been documented. Where these events are initiated and what cellular mechanisms are involved remain unknown. In this study, we established an experimental mouse model to evaluate the requirements for priming CD8+ T cells following the cross-presentation of intracranial Ag. Surprisingly, we find that even with a damaged blood-brain barrier, Ag presentation occurs in regional lymph nodes and not within the CNS itself. Only once the responding cells have expanded can they traffic to the site of CNS injury. Cross-presentation of intracranial Ag is efficient and the subsequent priming of CD8+ T cells is dependent on CD4+ T cell help and CD40 signaling in host APCs. Our findings have important implications for the initiation of T cell immune responses toward CNS Ags.